An Overview of Mechanical Tests for Polymeric Biomaterial Scaffolds Used in Tissue Engineering - Vazquez, Oscar Robles; Avila, Ignacio Orozco; Díaz, Juan C. Sánchez; Hernandez, Elena (Journal of Research Updates in Polymer Science, 2016)
Mechanical characterization of polymeric biomaterial scaffolds is essential to allow biomaterials that interface with tissues and tissue engineered constructs to be developed with appropriate mechanical strength. However, the fragility of these materials makes their mechanical characterization in a quantitative manner highly challenging. Here we report an overview of testing techniques for the characterization of mechanical properties of films, membranes, hydrogels and fibers commonly used as scaffolds in tissue engineering applications.